2023
DOI: 10.1097/mop.0000000000001241
|View full text |Cite
|
Sign up to set email alerts
|

Prebirth effects of climate change on children's respiratory health

Abstract: Purpose of reviewTo date, there is no evidence that humanity will implement appropriate mitigation measures to avoid the catastrophic impact of climate change on the planet and human health. Vulnerable populations such as pregnant women and children will be the most affected. This review highlights epidemiologic data on climate change-related prenatal environmental exposures affecting the fetus and children's respiratory health.Recent findingsResearch on outcomes of prenatal exposure to climate change-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Exposure during pregnancy to air pollution generated by burning fossil fuel, and extreme heat, is associated with hypertensive disorders, low birth weight, preterm birth, and affects foetal brain and lung development [ 13 ]. One meta-analysis concluded that the odds of preterm birth rose by 5% per 1°C increase in temperature and by 16% during heatwave vs non-heatwave days; therefore, there is greater risk with greater exposure and severity [ 14 ].…”
Section: Climate Change Is An Important Determinant Of Health Across ...mentioning
confidence: 99%
“…Exposure during pregnancy to air pollution generated by burning fossil fuel, and extreme heat, is associated with hypertensive disorders, low birth weight, preterm birth, and affects foetal brain and lung development [ 13 ]. One meta-analysis concluded that the odds of preterm birth rose by 5% per 1°C increase in temperature and by 16% during heatwave vs non-heatwave days; therefore, there is greater risk with greater exposure and severity [ 14 ].…”
Section: Climate Change Is An Important Determinant Of Health Across ...mentioning
confidence: 99%